Working and ageing : guidance and counselling for mature learners - (:unkn) unknown (Publications Office of the European Union, 2011)
"Population ageing is one of the most significant developments in Europe in the next decades. Guidance and counselling in supporting longer and more satisfying careers in ageing societies is important and has potential. This publication reviews factors contributing to successful active ageing from various angles. It examines contemporary approaches to guidance and counselling and presents several good practice examples of measures and practices launched in EU Member States. Successful approaches to guidance and counselling encompass a lifecycle perspective, are responsive and comprehensive and are supported by all stakeholders involved. The analysis and results reveal encouraging signs of progress, but at the same time indicate that much remains to be one to promote integration of ageing workers into the labour market and society." (Hrsg., BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.1.1 Demografie; P 1.8 Ältere; L 5 Beratung & Orientierung; I 2.2 Europa; Arbeitsmarkt; Beschäftigungsentwicklung; Demografischer Wandel; Älterer Arbeitnehmer; Beschäftigungsfähigkeit; Intergenerationelles Lernen; Lernberatung; Best practice; Europa